2010
DOI: 10.1021/ja102739b
|View full text |Cite
|
Sign up to set email alerts
|

Quantized Folding of Plasmid DNA Condensed with Block Catiomer into Characteristic Rod Structures Promoting Transgene Efficacy

Abstract: Highly regulated folding of plasmid DNA (pDNA) through polyion complexation with the synthetic block catiomer, poly(ethylene glycol)-block-poly(L-lysine) (PEG-PLys), was found to occur in such a way that rod structures are formed with a quantized length of 1/2(n + 1) of the original pDNA length folding by n times. The folding process of pDNA was elucidated with regard to rigidity of the double-stranded DNA structure and topological restriction of the supercoiled closed-circular form, and a mechanism based on E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 40 publications
(53 reference statements)
7
89
0
Order By: Relevance
“…It was shown that tuning steric forces was critical in obtaining 1-D nanostructures of precisely controlled length, by preventing buckling or condensation of the DNA template. The observations were consistent with the folding model for DNA condensation suggested by Kataoka, 220 derived from a mechanism based on Euler's buckling theory. 221 The templated self-assembly and supramolecular polymerization into 1-D filaments using oligonucleotides is a powerful strategy to produce uniform materials of well-defined size and shape, with a high degree of fidelity.…”
Section: Biomimetic Templated Polymerizationsupporting
confidence: 88%
“…It was shown that tuning steric forces was critical in obtaining 1-D nanostructures of precisely controlled length, by preventing buckling or condensation of the DNA template. The observations were consistent with the folding model for DNA condensation suggested by Kataoka, 220 derived from a mechanism based on Euler's buckling theory. 221 The templated self-assembly and supramolecular polymerization into 1-D filaments using oligonucleotides is a powerful strategy to produce uniform materials of well-defined size and shape, with a high degree of fidelity.…”
Section: Biomimetic Templated Polymerizationsupporting
confidence: 88%
“…Increasing the N/P ratio led to ad ecreased electrophoretic mobility of the product bands up to N/P = 1, from whereon the DOPMs migrated towards the cathode (Figure 2a). As imilar discrete folding in PMs has also been observed in double-stranded DNA [49] and suggests that for applications where high rigidity and strict shape control are needed, reinforced multilayer structures should be used. [48] Thet SEM images revealed intact structures where the shape of the DOPMs was strictly dictated by the underlying DNAorigami core.The only exception was the flat RO,which was protected as well, but which was also folded in half along the helical axis in more than 50 %o ft he cases ( Figure S4).…”
mentioning
confidence: 77%
“…The N/P ratio was â« in our experiments because transfection rates were low at N/P below 10. Interestingly, at N/P ratios of 1.0, an impact on circular plasmid tertiary structure has been reported using a different polycationic polymer (19). Particle size and shape are important variables in the cell biology of endocytosis and phagocytosis (20).…”
Section: Discussionmentioning
confidence: 99%